Modal identification of structures from ambient vibration, free vibration and seismic response data via a subspace approach. - Huang, C.S (Earthquake engineering & structural dynamics.)
This work presents a unified procedure for determining the natural frequencies, modal damping ratios and modal shapes of a structure from its ambient vibration, free vibration and earthquake response data. To evaluate the coefficient matrices of a state space model, the proposed procedure applies a subspace approach cooperating with an instrumental variable concept. The dynamic characteristics of a structure are determined from the coefficient matrices. The feasibility of the procedure is demonstrated through processing an in situ ambient vibration measurement of a five storey steel frame, an impulse response measurement of a three span continuous bridge and simulated earthquake responses of five storey steel frames from shaking table tests. The excellent agreement of the results obtained herein with those published previously confirms the feasibility of the present procedure.